Assessment, Analytics, and Analysis: Demonstrating the Impact of LMS Embedded Librarians on Student Learning. Issue 1 (3rd April 2019) - Tumbleson, Beth; Burke, John; Long, Jessica
Abstract: Librarians are committed to supporting teaching, learning, and research. They are equally committed to supporting student success and retention. Demonstrating the impact that learning management system (LMS) embedded librarians make on student learning has been difficult to correlate, however. Studies that assess this connection, using qualitative and quantitative data have been undertaken in recent years. In a university regional campus library study conducted in 2016–2017, LMS embedded librarians explored the relationship between student learning and information literacy instruction, relying primarily on a customized LMS embedded librarian page of library resources and learning objects. They used a rubric to assess student research papers and bibliographies, LMS course analytics, instructors' grades, and student feedback. This article reviews the literature and their methodology, challenges, and findings. They wish to guide colleagues, committed to assessing how librarians contribute to student learning, in selecting assessment approaches and validate their instructional role.